Heart failure induced by cancer therapies: focus on targeted agents, mechanisms, risk prediction, and clinical management - Xiao, Lifeng; Lin, Xiaoluan; Yang, Zhining; Lin, Baihan; Xie, Renxian (Frontiers in Pharmacology, 2026)
Targeted therapies have revolutionized oncology but are accompanied by significant cardiovascular complications, with heart failure being a major dose-limiting toxicity. This review primarily focuses on heart failure induced by targeted anticancer agents, while also contextualizing findings with insights from classical chemotherapeutics and radiotherapy where they inform mechanistic understanding or combination regimen management. We detail the multifaceted pathophysiological mechanisms, which vary by drug class, including direct cardiomyocyte injury via HER2/ErbB signaling disruption, mitochondrial dysfunction, oxidative stress, and novel pathways such as ferroptosis and autophagy dysregulation. The review evaluates strategies for risk assessment, highlighting the utility and limitations of clinical tools like Heart Failure Association-International Cardio-Oncology Society (HFA-ICOS) risk score, and acknowledges that while biomarkers and advanced imaging parameters like global longitudinal strain (GLS) are often reported to have high sensitivity for early detection, their performance can vary depending on the specific definitions of cardiotoxicity used and the clinical context. Current management paradigms are discussed, encompassing pharmacological cardioprotection, treatment modification protocols, and the safe continuation of therapy with concomitant cardiac medications. Furthermore, we explore emerging strategies from traditional natural products and gene-based therapies to advanced drug delivery systems aimed at providing targeted cardioprotection. Finally, future perspectives are outlined, focusing on personalized risk prediction through multi-omics and artificial intelligence, and the development of novel therapeutics with improved cardiovascular safety profiles. This mini review underscores the importance of a multidisciplinary cardio-oncology approach to optimize both oncological efficacy and long-term cardiovascular health for cancer patients.